2022
DOI: 10.1007/s00586-021-07103-9
|View full text |Cite
|
Sign up to set email alerts
|

Distance to first symptoms measured by the 6-min walking test differentiates between treatment success and failure in patients with degenerative lumbar disorders

Abstract: Purpose The smartphone-based 6-min walking test (6WT) is an established digital outcome measure in patients undergoing surgery for degenerative lumbar disorders (DLD). In addition to the 6WTs primary outcome measure, the 6-min walking distance (6WD), the patient’s distance to first symptoms (DTFS) and time to first symptoms (TTFS) can be recorded. This is the first study to analyse the psychometric properties of the DTFS and TTFS. Methods Forty-nine consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…19,23,[41][42][43][44][45] Smartphone administration of these assessments could allow for more frequent testing and a reduction of Hawthorne effects. Zeitlberger et al 46 examined more granular measures of a smartphone app-based 6WT in patients with degenerative lumbar disorders. They found that the time to first symptoms (TTFS) and distance to first symptoms (DTFS) improved from baseline at 6 weeks postoperatively and that DTFS was better able to differentiate between satisfied and unsatisfied patients than 6WT alone.…”
Section: Adaptation Of Current Clinical Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,23,[41][42][43][44][45] Smartphone administration of these assessments could allow for more frequent testing and a reduction of Hawthorne effects. Zeitlberger et al 46 examined more granular measures of a smartphone app-based 6WT in patients with degenerative lumbar disorders. They found that the time to first symptoms (TTFS) and distance to first symptoms (DTFS) improved from baseline at 6 weeks postoperatively and that DTFS was better able to differentiate between satisfied and unsatisfied patients than 6WT alone.…”
Section: Adaptation Of Current Clinical Assessmentsmentioning
confidence: 99%
“…Ahmad et al 49 examined smartphone mobility data during a two-year perioperative period in patients who underwent elective lumbar decompressive surgery. They describe 5 clinical stages characterized by mobility patterns: preoperative baseline, preoperative presentation/ decline, immediate postoperative recovery, full recovery, and possible 49 Ahmad 2021 50 Basil 2021 3 Boaro 2021 26 Cote 2019 22 Maldaner 2021 41 Zaldivar-Jolissaint 2021 51 Zeitlberger 2022 46 Zeitlberger 2021 42 Postoperative secondary decline. These stages correlated with clinical documentation of the patients' courses.…”
Section: Surgical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation